3x-66=9x

Simple and best practice solution for 3x-66=9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-66=9x equation:


Simplifying
3x + -66 = 9x

Reorder the terms:
-66 + 3x = 9x

Solving
-66 + 3x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-66 + 3x + -9x = 9x + -9x

Combine like terms: 3x + -9x = -6x
-66 + -6x = 9x + -9x

Combine like terms: 9x + -9x = 0
-66 + -6x = 0

Add '66' to each side of the equation.
-66 + 66 + -6x = 0 + 66

Combine like terms: -66 + 66 = 0
0 + -6x = 0 + 66
-6x = 0 + 66

Combine like terms: 0 + 66 = 66
-6x = 66

Divide each side by '-6'.
x = -11

Simplifying
x = -11

See similar equations:

| 1+k=3k-1 | | -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 | | 4=p-1 | | X-1.25=3.5 | | 0.5-0.5j=0 | | 2(h+3)+1=9 | | 0=-9(b-1) | | x^2+3-12=0 | | 12x^3-8x^2-35x+6=0 | | (2x+4)(x)=20 | | X+0.3=-0.4 | | -6.75=x+5.4 | | 4(2x+4)=10x+15-2x+17 | | 265=-5x | | 14=k+9 | | 5-6w=-13 | | 9x-2+55=13+14x | | -4x-36=-72 | | -16+m=-20 | | 5=9+4x | | 0.5(4x+8)(x)=20 | | 4c=16.8 | | -19=x-17 | | 6y-(2y-5y)=29 | | 1.48(k+3)=5.92 | | b+14=1 | | d+(-7)=12 | | 6x+3=98-3x+6 | | 7+1-6x+3x=3x-5x |

Equations solver categories